Comment on “Io Hot Spot Distribution Detected by Juno/JIRAM” by Zambon et al. - Ashley Gerard Davies (Geophysical Research Letters)
Abstract The distribution of volcanic thermal emission on Io might reflect the location and magnitude of tidal heating, so it is important to accurately identify Io’s volcanoes to enable robust interior modeling. Zambon et al. (2023, https://doi.org/10.1029/2022gl100597) “Io Hot Spot Distribution Detected by Juno/JIRAM,” Geophysical Research Letters, 50, e2022GL100597 (2023) report the positions of hot spots on Io at high latitudes that are apparently spurious. This appears to be due to mis‐registration of JIRAM images to a frame of reference, leading to the same hot spot being located in different positions on Io’s surface. Other hot spots are not identified. The outcome of these additional and missing detections is a skewing of volcanic activity toward high latitudes, suggesting more polar activity than that seen at lower latitudes. This distribution of thermal sources would support a preponderance of deep mantle tidal heating, a conclusion not supported by other analyses of the same data.